Vegetation quality as indicator of desertification in the Paraguana Peninsula, Venezuela (Ágora de Heterodoxias, 2016)
Through the development of this work the index of vegetation quality index (IVQ) is determined as an expression of the degree of vulnerability to desertification in the Paraguana Peninsula. The calculation of IVQ was based on the integration of the following indicators: vegetation resistance to drought, vegetation protection against erosion and vegetation cover. This raises a functional definition of the different plant communities identified in the Paraguana Peninsula, based on these three criteria for determining the quality of vegetation. The integration is performed by calculating a geometric mean, using numerical values that rated the quality of the different indices in relation to their ability to influence the vulnerability of the territory to the desertification process. The process of information and representation of the results was performed using spatial analysis tools with GIS. Results show that about 3% of the area of the Peninsula had low quality of vegetation, which was strongly associated scrub communities which happen to be the most vulnerable to degradation processes. 11.4% of the territory is covered by plant communities that have high quality or low vulnerability to desertification risk. The remaining 85.6% of the peninsula is covered by both scrub and shrub plant communities, providing moderate quality plant resources but are potentially vulnerable to desertification process, product of management that are receiving these areas depending on the goat farming extensively and changing land use to intensive horticultural systems that promote processes of salinization and erosion, which generate short-term total loss of vegetation cover.
Keywords: vegetation quality; canopy cover; desertification; geographic information system